Estimation of Paddy Productivity at Subdistrict Level using Geoadditive Small Area Estimation Model in Ponorogo Regency - Maulana, Arswenda Putra; Prasetyo, Rindang Bangun (Inferensi, 2024)
Paddy is the most important food crop in the world and it is the source of food needed by more than half of the population on a global scale. However, the world is experiencing the threat of a food crisis, so the Indonesian government continues to be committed to increasing national paddy production and ensuring food sufficiency in the country by implementing food self-sufficiency programs in each region. Paddy productivity data can be used as one of the government's benchmarks to assess the success of the food self-sufficiency program, but BPS-Statistics Indonesia only provides data on paddy productivity up to the district/cities level. Therefore, this study aims to estimate paddy productivity at sub-district level using the Geo-SAE method. Based on the research results, the estimation of the average paddy productivity in Ponorogo Regency in 2022 using Geo-SAE was obtained at 5.8 tons/ha and resulted in a smaller RSE value compared to the direct estimation at sub-district level. This indicates that the Geo-SAE method has better precision than the direct estimation method. Meanwhile, additional result from estimation of paddy productivity shows that in Ponorogo Regency in 2022 there is a large rice surplus. Therefore, it can be said that Ponorogo Regency is experiencing a very good food sufficiency condition.